Insurance-Mediated Disparities in Gynecologic Oncology Care. Issue 2 (February 2022) - Bodurtha Smith, Anna Jo; Pena, Daniella; Ko, Emily
Abstract : With 102, 000 new cases of gynecologic cancer, 30, 000 associated deaths annually, and increasing rates of endometrial cancer, gynecologic cancer is a growing problem. Although gynecologic cancer care has advanced significantly in the past decade owing to new therapeutics and specialized training in radical surgery, even insured women face major barriers to accessing and affording quality gynecologic cancer care. This commentary reviews current literature on insurance-mediated disparities in gynecologic cancer and provides education to clinicians on barriers to care. One third of women with a gynecologic cancer never see a gynecologic oncologist. Up to 40% of Medicare Advantage plans lack an in-network gynecologic oncologist, and 33% of private insurance plans do not include an in-network National Cancer Institute-accredited cancer center, limiting access to surgical advances and clinical trials. Women with Medicaid insurance and gynecologic cancer are 25% less likely to receive guideline-concordant care. Among insured women, 50% experience financial toxicity during gynecologic cancer treatment, and costs may be even higher for certain Medicare enrollees. Addressing these insurance-mediated disparities will be important to help our patients fully benefit from the scientific advances in our field and thrive after a gynecologic cancer diagnosis. Abstract : Insurance coverage has lagged behind improvements in gynecologic cancer care, with one third of women never seeing a gynecologic oncologist and half experiencing financial toxicity during cancer treatment.